2021
DOI: 10.1186/s12913-021-06244-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the behavioral intention to use a mobile nursing application by nurses in China

Abstract: Background Although a mobile nursing application has began to adopt in nursing, few studies have focused on nurses’ behavioral intention of it. The objective of this study is to gain insight into the behavioral intention of nurses, i.e. chinese nurses of the future, to use a mobile nursing application. This study adopted an extension of the Unified Theory of Acceptance and Use of Technology to examine Chinese nurses’ acceptance of a mobile nursing application. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 70 publications
8
27
2
1
Order By: Relevance
“…The negative but significant impact of perceived risk on the intention to use mobile health services agrees with the findings of other studies that reported that perceived risk is a significant determinant of the intention to use ( 3 , 122 , 123 ). This finding is a departure from studies that revealed perceived risk showed an insignificant impact on behavioral intention to use ( 124 ). The validated impact of perceived risk on recommendation intentions of m-health services seems to be a key finding of this study, since no study has, so far, experimented on this relationship.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The negative but significant impact of perceived risk on the intention to use mobile health services agrees with the findings of other studies that reported that perceived risk is a significant determinant of the intention to use ( 3 , 122 , 123 ). This finding is a departure from studies that revealed perceived risk showed an insignificant impact on behavioral intention to use ( 124 ). The validated impact of perceived risk on recommendation intentions of m-health services seems to be a key finding of this study, since no study has, so far, experimented on this relationship.…”
Section: Discussioncontrasting
confidence: 92%
“…The positive significant findings of mobile self-efficacy on the intention to use support findings that show that self-efficacy is a significant determinant of the intention to adopt ( 26 , 97 ). Other research has further confirmed that the level of self-efficacy demonstrated toward the utilization of technology drives the intention to use such applications ( 124 ) but contradicts results indicating that self-efficacy does not influence the intention to use ( 125 ). Again, mobile self-efficacy was found to be significant in determining both perceived usefulness and perceived ease of use of m-health services.…”
Section: Discussionmentioning
confidence: 95%
“…Prior studies have explored various factors that affect the acceptance of information technologies [ 20 ]. Recently, studies focusing on mHealth have grown rapidly and the value of mHealth based on mobile technologies has gradually been recognized [ 21 , 22 ]. The use of mobile phones and the development of mHealth apps have aroused the interest of researchers in information systems [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has a positive relationship with trust in forming online purchase intentions (Guru, Nenavani, Patel, & Bhatt, 2020). On the other hand, some research results indicate that the perceived risk negatively influences the intention to use technology (Lv, 2021;Pan & Gao, 2021;Akdur, Aydin, & Akdur, 2020). Perceived risk had no significant effect on behavioral intention to use mobile nursing applications (Pan & Gao, 2021).…”
Section: Relationship Between Perceived Risks and Trustmentioning
confidence: 98%
“…On the other hand, some research results indicate that the perceived risk negatively influences the intention to use technology (Lv, 2021;Pan & Gao, 2021;Akdur, Aydin, & Akdur, 2020). Perceived risk had no significant effect on behavioral intention to use mobile nursing applications (Pan & Gao, 2021). Likewise, there is no significant relationship between perceived risk and behavioral intention to use the mHealth application (Akdur, Aydin, & Akdur, 2020).…”
Section: Relationship Between Perceived Risks and Trustmentioning
confidence: 99%